Metacognition, learning, & Socrates : asking questions to foster entrepreneurial minds - Tarasanski, Pavlos (2020)
Scholars have criticized the field of entrepreneurship education for ignoring cognitions relevant to the discipline in the past and focusing on traditional pedagogies when teaching it. To fill both gaps, an educational intervention was conducted with the purpose of increasing high school students’ metacognition - which forms the foundation of an entrepreneurial mindset. The Socratic Method (SM) was chosen as the method of instruction, which is a constructivist pedagogical approach built on stimulating critical thinking and dialogue. The sample included 15 students with a mean age of 16.6. The intervention was conducted by me, took place in a language school in Russia, and lasted for three consecutive days. Mixed methods were applied to collect and analyse data. For the quantitative part, self-reported pre and post measurements of student metacognition were obtained using the measure of adaptive cognition (MAC), followed by a paired-sample t-test. On average, students’ metacognition had moderately increased after the course as measured by the five variables of the MAC, with changes in goal orientation not being statistically significant. The effect size of the intervention was strong, indicating that the increases as measured by the MAC were caused by the intervention itself. To understand the ways in which the SM contributed to the increase in student metacognition, qualitative data was collected in the form of students’ learning diaries, resulting in triangulation. The qualitative findings highlighted several specific mechanisms in which the SM contributes to students' metacognition, those being consistent with the constructivist ideology. There seems to be potential in utilizing constructivist pedagogies within entrepreneurial classrooms to foster metacognition, however further research is needed that will include larger samples and control groups to push for generalizability and superiority over traditional pedagogies. In addition, attention was brought to whether it is better to measure metacognition quantitatively or assess it qualitatively. The study's contribution resides within its piloting nature where the SM is used to increase metacognition within an entrepreneurial classroom, thus trying to bridge the two gaps mentioned in the beginning of this abstract.